Diazinon exposure reduces bone mineral density in adult and immature rats: A histomorphometric and radiographic study. (November 2021) - Bazmi, Mahdiye; Elahifar, Mahbubeh; Lari, Roya; Shahri, Naser Mahdavi
Diazinon has been widely used as a domestic and agricultural pesticide. This study examined the effects of diazinon on bone mineral density (BMD) of mature and immature rats. For this purpose, 24 adult Wistar rats (male; 8 weeks old) were initially divided into four groups ( n = 6). Corn oil was used as the control while diazinon at 15, 30, and 45 mg/kg in corn oil was given to mature rats via gavage per day. Since these dosages were lethal for the immature rats, 12 immature Wistar rats (male; 4 weeks old) ( n = 6) were gavaged with corn oil as control and 5 mg/kg of diazinon in corn oil. The animals were sacrificed on day 28 with their left femur bones removed for histomorphometric studies. BMD was measured in the right femur, using standardized radiographs in the femoral head, femoral neck, greater trochanter, and shaft. The Image J Program was used for measuring the bone lamellae and epiphyseal growth plates. The results of this study for the first time revealed that diazinon reduced BMD in both adults and immature rats. Diazinon exposure was associated with diminished trabecular and cortical bone density. Correspondingly, our results indicated that in immature rats, DZN led to the reduction in the epiphyseal growth plate width, both in the proliferation and hypertrophic zones. These results suggested that diazinon might be associated with impaired bone longitudinal growth as well as bone metabolism in adults.